Develop The Learner’s Oral Skills by Singing English Songs (Journal of Pedagogical Inventions and Practices, 2022)
The scientific papers related to the use of musical works in the course of teaching English. It is noted that the differences, as a rule, are limited to observations and recommendations of a private nature, as well as an appeal to new educational material (previously unused pieces of music). The authors come to the conclusion that the use of songs in foreign language lessons should not be taken as an "educational panacea" or the main teaching method. Listening skills are recommended to be developed using traditional exercises that have been proven over many decades